Pregnancy rates and outcomes in women with and without MS in the United States. (23rd October 2018) - Houtchens, Maria K.; Edwards, Natalie C.; Schneider, Gary; Stern, Kevin; Phillips, Amy L.
Abstract : Objective: To compare pregnancy prevalence and complications in women with and without multiple sclerosis (MS). Methods: This retrospective US administrative claims study used data from January 1, 2006, to June 30, 2015. All data for women with MS were included. A nationally representative 5% random sample from approximately 58 million women without MS was used to compute the dataset. Annual pregnancy rates, identified via diagnosis/procedure codes and adjusted for covariates, were estimated via logistic regression. Claims for pregnancy and labor/delivery complications were compared using propensity score matching. Results: From 2006 to 2014, the adjusted proportion of women with MS and pregnancy increased from 7.91% to 9.47%; the adjusted proportion without MS and with pregnancy decreased from 8.83% to 7.75%. The difference in linear trend (0.17% increase and 0.15% decrease in per-annum pregnancy rates) was significant ( t statistic = 7.8; p < 0.0001). After matching (n = 2, 115 per group), a higher proportion of women with MS than without had claims for premature labor (31.4% vs 27.4%; p = 0.005), infection (13.3% vs 10.9%; p = 0.016), cardiovascular disease (3.0% vs 1.9%; p = 0.028), anemia/acquired coagulation disorders (2.5% vs 1.3%; p = 0.007), neurologic complications (1.6% vs 0.6%; p = 0.005), sexually transmitted diseases (0.4% vs 0.1%; p = 0.045), acquired fetal damage (27.8% vs 23.5%; p = 0.002), and congenital fetal malformations (13.2% vs 10.3%; p = 0.004). Conclusions: Pregnancy rates in this population of women with MS have been increasing. High rates of claims for several peripartum complications were observed in women with and those without MS. Claims data provide knowledge of interactions patients have with the health care system and are valuable initial exploratory analyses.